2015
DOI: 10.1089/dia.2014.0290
|View full text |Cite
|
Sign up to set email alerts
|

Salient Characteristics of Youth with Type 1 Diabetes Initiating Continuous Glucose Monitoring

Abstract: Objective: Consistent continuous glucose monitoring (CGM) use is a challenge in youth with type 1 diabetes. This study aimed to investigate patient and family behavioral and clinical characteristics associated with interest in implementing CGM. Research Design and Methods: In a cross-sectional study, we compared 120 youth interested in starting CGM (the CGM group) with a general sample of 238 youth with type 1 diabetes (the Standard group). Youth and their parents completed validated surveys assessing adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Patients with good diabetes management, evaluated by the Self‐Care Inventory, the Diabetes Behavior Rating Scale, the Diabetes Self‐Management Profile, the Diabetes Interview, or a composite score, have lower HbA1c levels . In contrast, missing injections or poor self‐monitoring of blood glucose was correlated with increased HbA1c level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with good diabetes management, evaluated by the Self‐Care Inventory, the Diabetes Behavior Rating Scale, the Diabetes Self‐Management Profile, the Diabetes Interview, or a composite score, have lower HbA1c levels . In contrast, missing injections or poor self‐monitoring of blood glucose was correlated with increased HbA1c level.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size range is 70 to 30 708 patients with a median sample size of 210 T1D patients. Thirty‐two studies were performed in several European countries, 31 in USA, one in Canada, three in Israel, and the rest in other countries (one in Japan, one in New‐Zealand, three in Turkey, one in Australia, and three are multinational). Most studies (54 studies) were performed on T1D children (median of mean age reported in articles 12.5 [range: 4.1‐17.7]), 22 included both children and young adults (median of mean age of 14.8 [range: 10.1‐21.6]), and one included only young adults (mean age of 19.4 ± 0.9 [range: 18‐21]).…”
Section: Resultsmentioning
confidence: 99%
“…12 In youth, the following characteristics predict interest in starting CGM: lower A1C, more frequent BG monitoring, greater likelihood of being on an insulin pump, and having a two-parent family, greater diabetes adherence, lower diabetes-specific family conflict, and higher quality of life. 40 Finally, being non-Hispanic white is also associated with more frequent CGM use in youth younger than 13 years old. 12 For SAP, a low A1C, and frequency of use of the sensor predicts more frequent long-term use.…”
Section: Demographic Characteristics Of Technology Usersmentioning
confidence: 98%
“…I n a very interesting article in the current issue of Diabetes Technology & Therapeutics, Telo et al 1 found that only 28% of young patients with type 1 diabetes (T1D) who were offered continuous glucose monitoring (CGM) accepted the invitation. Compared with a control group from the same diabetes center, the subjects who declined were less likely to use an insulin pump, had a higher hemoglobin A1c level, carried out blood glucose (BG) monitoring less often, were generally less adherent to their diabetes program, had a higher rate of family conflict related to diabetes, and returned lower quality of life values by questionnaire.…”
mentioning
confidence: 99%